2012
DOI: 10.1177/0748233712457447
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and oxidative stress in chromium-exposed tannery workers in North India

Abstract: Trivalent chromium (Cr) is an environmental contaminant, which is extensively used in tanning industries throughout the world and causes various forms of health hazards in tannery workers. Therefore, a cross-sectional study design was used to evaluate the DNA damage and oxidative stress condition in tannery workers exposed to Cr in North India. The study population comprised 100 male tanners in the exposed group and 100 healthy males (no history of Cr exposure) in the comparable control group. Baseline charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…However, studies of tannery workers in various countries have found significant differences between the number of CAs in exposed individuals compared to unexposed controls (Hilali et al, 2008;Monteiro Neto et al, 2010). Other reports of alterations to genetic material, such as an increase in DNA lesions, have confirmed these results (Balachandar et al, 2010;Ambreen et al, 2014). In our study, dicentric, tricentric, and ring-shaped chromosomes were the most frequently observed aberrations (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, studies of tannery workers in various countries have found significant differences between the number of CAs in exposed individuals compared to unexposed controls (Hilali et al, 2008;Monteiro Neto et al, 2010). Other reports of alterations to genetic material, such as an increase in DNA lesions, have confirmed these results (Balachandar et al, 2010;Ambreen et al, 2014). In our study, dicentric, tricentric, and ring-shaped chromosomes were the most frequently observed aberrations (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…The formation of DNA adducts creates instability in the replication fork, leading to chromosomal breaks (Kirsch-Volders et al, 2014). Moreover, several studies in which chromium levels have been measured in tannery workers have found large amounts in biological samples (Randall and Gibson, 1989;Stupar et al, 1999;Medeiros et al, 2003;Ambreen et al, 2014).…”
Section: Groupmentioning
confidence: 99%
“…The workers are exposed mainly through inhalation of Cr (VI) (Stout et al, 2009). Different studies accomplished with tanneries, cement, and chrome-plating workers had related the exposure of Cr (VI) to various skin and lung diseases as well as alterations in oxidative stress parameters (Caglieri et al, 2006;Ambreen, Khan, Bhadauria, & Kumar, 2014;Elhosary, Maklad, Soliman, El-Ashmawy, & Oreby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…©2019 Reviews in Agricultural Science vulnerable to several health problems along with DNA damage (Rastogi et al, 2008;Ambreen et al, 2014;Ali et al, 2015). We reported that individuals who are exposed to occupational health hazards are under oxidative stress.…”
mentioning
confidence: 99%